Is blended e-learning as measured by an achievement test and self-assessment better than traditional classroom learning for vocational high school students? - Chi-Cheng Chang (Athabasca University Press, 2014)
The purpose of this study is to examine the effects of blended e-learning on electrical machinery performance (achievement test and self-assessment). Participants were two classes of 11th graders majoring in electrical engineering and taking the electrical machinery class at a vocational high school in Taiwan. The participants were randomly selected and assigned to either the experimental group (n = 33) which studied through blended e-learning or the control group (n = 32) which studied through traditional classroom learning. The experiment lasted for five weeks. The results showed that (a) there were no significant differences in achievement test scores between blended e-learning and traditional learning; (b) students in the experimental group obtained significantly higher scores on self-assessment than students in the control group; (c) students’ scores on self-assessment were significantly higher after studying through blended e-learning than before. Overall, blended e-learning did not significantly affect students’ achievement test scores, but significantly affected their self-assessment scores.